2014
DOI: 10.1371/journal.pone.0093011
|View full text |Cite
|
Sign up to set email alerts
|

IL28B Polymorphisms and Clinical Implications for Hepatitis C Virus Infection in Uzbekistan

Abstract: AimsGenome-wide association studies highlighted single nucleotide polymorphisms (SNPs) within the IFNL3/IL28B locus predict the treatment outcome for patients with HCV. Furthermore, SNPs in newly discovered IFNL4 are shown to have population-specific correlation with spontaneous clearance of HCV. The aim of this study was to examine the prevalence and clinical significance of the outlined SNPs in a population from Central Asia, a multi-ethnic region with a developing economy and a high prevalence of HCV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…In the present study, when the HCV RNA levels analysed, neither SVR nor rs80999917 genotypes were associated by HCV RNA levels. These results are consistent with other studies, which presented similar results [29,36]. On the other hand, several studies reported mean HCV RNA level had a significantly higher in the carriers of rs8099917 G allele and the non-SVR group [22,27,32,35,40].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, when the HCV RNA levels analysed, neither SVR nor rs80999917 genotypes were associated by HCV RNA levels. These results are consistent with other studies, which presented similar results [29,36]. On the other hand, several studies reported mean HCV RNA level had a significantly higher in the carriers of rs8099917 G allele and the non-SVR group [22,27,32,35,40].…”
Section: Discussionsupporting
confidence: 92%
“…Asian and Caucasian patients with TT genotype had a 5.21-and a 2.54-fold greater chance of SVR than TT-negative patients [30]. The carriers of the nonresponders variants TG and GG had a higher risk for therapy failure than noncarriers [4,22,29,36]. This is in again agreement with our study; (OR, 11.10; 95% CI, 2.43-50.75; P < 0.001 for GG and OR, 4.00; 95% CI, 2.43-6.60; P < 0.001 for TG, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, a dinucleotide variant, ss469415590, in strong linkage disequilibrium with rs12979860 has been reported, which created a novel IFNL4 gene and has functional effects on the IL28B expression [Prokunina‐Olsson et al, ]. The identification of IFNL4 SNP has improved prediction rate of response to peg interferon and ribavirin therapy in HCV patients however, differences among various ethnic groups have been reported [Khudayberganova et al, ; Real et al, ]. Study of the ss469415590 and the IL28B SNPs genotyped in this study may help to better predict response to HCV treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, not the rs12979860 but the rs8099917 TT genotype had benefit from a shorter duration of combination therapy in HCV-1 patients (33). In Uzbekistan, SNP rs8099917 was found the most predictive of outcome for Central Asians (18) and in chile, all the three genotypes (the IL28B rs12979860 CC, rs12980275 AA and rs8099917 TT) have been found frequent in patients with SVR compared to null responders (38%, 44% and 50% vs. 2%, 8.2% and 8.2%, respectively) (34). Two recent studies have failed to show such an association: status of IL-28B polymorphism neither affected nor had an impact on virologic response in France and Japan (35,36).…”
Section: Discussionmentioning
confidence: 97%
“…SNPs of the IL28B gene has been extensively described in the literature but allele frequencies, in particular rs809917, differs somewhat between world-wide populations (17,18,19,20). Therefore, the predictive power of SNPs may vary between different cohorts.…”
Section: Introductionmentioning
confidence: 99%